« For the Childlike is the Divine » : la quête de la jeunesse éternelle dans les contes et romances de George MacDonald - Benjamine Toussaint-Thiriet (Cahiers Victoriens et Edouardiens)
A link may be found between the Bildungsroman genre and MacDonald’s fairy tales and romances because of the obvious didactic function of the latter. In the Bildungsroman, the maturation process of the main protagonist is seen as a rather positive phenomenon, focusing on its growing up (both physically and mentally) rather than growing old. In MacDonald’s works, on the contrary, becoming an adult is often perceived as a negative experience, a regression rather than an evolution from a moral and spiritual point of view. Old age, on the other hand, is depicted as a new birth, physical beauty and a youthful appearance often mirroring the rejuvenation of the heart and soul of the characters. MacDonald’s vision of these three ages of man is based on his deep religious beliefs and the magical world created in his fairy tales and romances enables him to avoid the more pragmatic and pessimistic aspects in his depiction of the process of growing old. In fact the point is not so much about glorifying the wisdom of old age as praising the virtues of remaining everlastingly childlike, which is precisely the only quality MacDonald demanded from his readers, whatever their real age might be.